CLINICAL EFFECT OF DIODE LASER THERAPY AND CHLORHEXIDINE GEL 0.2% AS ADJUNCTS TO NON-SURGICAL PERIODONTAL THERAPY IN CASES OF CHRONIC PERIODONTITIS - MOHAMMED, LAVA OMAR; MOHAMMED, SAEED ALI (Journal of Duhok University, 2023)
Objectives: The aim of the current study is to compare the efficacy of a diode laser (940 nm) and chlorhexidine -gel 0.2% with that of conventional non-surgical mechanical treatment. Materials and methods: A group of patients with chronic periodontal disease are the subject of the current split-mouth -clinical trial Periodontal pocket- depth (PPD) of than 5 mm and more were used to categorize 180 tooth surfaces with moderate to severe periodontal disease into three categories. The entire mouth underwent periodontal treatment, which included scrubbing and root surface debridement. Using a split mouth design, (scaling and) root surface debridement alone were applied randomly to each quadrant while SRP with diode laser (Biolase) and SRP with 0.2% chlorhexidine- gel (perio Kin gel) were the test- groups. Results: As Compared to baseline, both of the study’s treatment modalities resulted in statistically - significant improvements in the assessed clinical parameters at one and three months. After three months there was statistically significant difference in PD, CAL, and BOP between/ the diode laser and the control- groups as well as between the diode laser group and the chlorhexidine- gel group. Conclusions: After 1 month of evaluation, the high intensity diode laser and chlorhexidine gel have not shown any additional benefits to the conventional periodontal treatment. Clinical relevance of diode laser therapy in conjunction with conventional scaling and root surface debridement seem to be superior in reducing probing depth, Clinical attachment level and bleeding on probing than SRP alone or SRP with Chlorhexidine gel 3 months after treatment